Analysis of The Implementation of Artificial Intelligence (AI) on The Satisfaction of Customers with Digital Banking Services - Juniar, Silvia Nursesa; Muttaqin, Aminullah Achmad (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to analyse the impact of Artificial Intelligence (AI) implementation on customer satisfaction in digital banking services in East Java. Expectancy Disconfirmation Theory (EDT) serves as the theoretical framework to assess how expectation, perceived performance, and Disconfirmation influence customer satisfaction with AI-based banking services. A quantitative approach was employed, collecting data through a digital questionnaire covering key variables: expectation, perceived performance, and Disconfirmation as independent variables, and customer satisfaction as the dependent variable. Multiple linear regression analysis was conducted to evaluate the contribution of each independent variable to customer satisfaction. Furthermore, instrument validity and reliability tests, along with classical assumption tests—including normality, multicollinearity, and heteroscedasticity tests—were performed to ensure the suitability of the regression model. The findings provide valuable insights into the role of AI in shaping customer satisfaction in digital banking and offer practical implications for financial institutions to optimize AI-driven banking services.